MENGUAK STRATEGI INDUSTRI KERAJINAN PERAK SUNSRI HOUSE OF JEWELRY MENEMBUS PASAR EKSPOR MELALUI E-COMMERCE - Manika Semara Ratih; I Nyoman Rasmen Adi (Media Bina Ilmiah, 2023)
This study aims to find out the strategy used by Sunsri House of Jewelry in penetrating the export market through e-commerce during the Covid-19 crisis. The type of research used was descriptive qualitative. This research was conducted on one of the MSMEs in Celuk Sukawati Gianyar Village, Bali, Sunsri House of Jewelry. Data collection in this study was carried out in three ways: through interviews, observations, and documentation. The technique used in selecting informants in this study was purposive sampling and selected the Sunsri House of Jewelry management team. Data analysis techniques were used through data reduction, presentation, and conclusion. Data validity techniques were used through source triangulation and method triangulation. The results showed that through the 4C strategy in the form of meeting needs according to consumer desires, competitive costs, as well as convenient, unique, and quality products, supported by online transaction facilities and variant channels of several types of communication connections between consumers that make it easier for consumers to interact with Sunsri House of Jewelry are effective enough to penetrate the export market.